The role of misclassification of exposure in the association between aspirin and nonsteroidal anti‐inflammatory drug use and keratinocyte cancers: reply from the authors. (13th August 2019) - Pandeya, N.; Olsen, C.M.; Whiteman, D.C.
Abstract : Linked Article : Abtahi et al . Br J Dermatol 2019; 181 :649 . Pandeya et al . Br J Dermatol 2019; DOI: 10.1111/bjd.17938 .